2017
DOI: 10.1111/nmo.13276
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia severity is related to the amplitude of distal contractile integral in patients with Jackhammer esophagus

Abstract: The DCI mediates dysphagia in patients with JE. Duration of symptoms affected hypercontractile DCI scores and aggravated perception of dysphagia indicating a progressive character of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 29 publications
5
38
0
1
Order By: Relevance
“…Therefore, a therapeutic approach like peroral endoscopic myotomy is regarded as suitable treatment in these individuals [24]. Confirmatory, our group emphasized that JE is of progressive clinical nature and may even mimic GERD by responding to PPI therapy [15,25]. It is obvious that these facts influence bariatric strategies or even limit postoperative outcomes after surgery.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, a therapeutic approach like peroral endoscopic myotomy is regarded as suitable treatment in these individuals [24]. Confirmatory, our group emphasized that JE is of progressive clinical nature and may even mimic GERD by responding to PPI therapy [15,25]. It is obvious that these facts influence bariatric strategies or even limit postoperative outcomes after surgery.…”
Section: Discussionmentioning
confidence: 83%
“…High-resolution impedance manometry was performed using a solid-state catheter with 32 circumferential pressure transducers at 1-cm intervals and dual impedance sensors (Sandhill Scientific, Highlands Ranch, CO, USA) as previously described [15]. Esophageal body motility was assessed with 10 liquid swallows of 5 ml at 30-s intervals.…”
Section: High-resolution Impedance Manometrymentioning
confidence: 99%
“…Diagnoses of JE comprised 1.97% [95% CI: 1.39%-2.78%; Cochran's Q = 81.7, I 2 = 87.8%] of HRM studies based on eleven studies reporting this data in unselected symptomatic individuals referred for HRM [16][17][18][19][20][21][22][23][24][25][26] ( Figure 2). On sensitivity analysis, we found that Zuluaga…”
Section: Demographicsmentioning
confidence: 99%
“…The negative outcome of this study can be interpreted in two ways. The authors concluded that the study was negative because hypercontractile esophageal motility disorders have a benign natural disease course, with spontaneous improvement after three months in line with some but not all previous reports . Another interpretation could be that patients with hypercontractile esophageal motility disorders have functional esophageal symptoms that are not related to the esophageal hypercontractility, and therefore, these symptoms are not responding to treatment of the hypercontractility.…”
mentioning
confidence: 55%
“…The authors concluded that the study was negative because hypercontractile esophageal motility disorders have a benign natural disease course, with spontaneous improvement after three months in line with some but not all previous reports. [3][4][5][6] Another interpretation could be that patients While pooled together in this study, type III achalasia is probably different from jackhammer and DES, as the relationship between symptoms and abnormal motility seems clearer in type III achalasia and more data on natural history and development to other types of achalasia is available. For DES and jackhammer, a substantial subset of these patients may have functional symptoms that therefore do not respond to reduction of hypercontractility with botulinum toxin.…”
mentioning
confidence: 90%